Nonmetallic Mineral as the Carrier of TiO2 Photocatalyst: A Review - Xie, Yan; Wang, Jiao; Ren, Fengguo; Shuai, Huan; Du, Gaoxiang (Frontiers in Catalysis, 2022)
Titanium dioxide has a broad application prospect in solving environmental pollution problems. By changing the titanium dioxide load on the nonmetallic mineral carrier, the catalytic and application performance of titanium dioxide can be improved. This paper describes the catalytic mechanism of titanium dioxide, as well as the research and application progress of various nonmetallic mineral materials supported by titanium dioxide, and prospects the development trend in the future.